2002
DOI: 10.1248/bpb.25.483
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Cytotoxic Activities of Five Veronica Species.

Abstract: In the flora of Turkey, the genus Veronica L. (Scrophulariaceae) is represented by 79 species, 26 of which are endemic.1) In traditional Turkish medicines, some Veronica species are used as diuretics and in the healing of wound.2) In addition, several Veronica species are used to treat cancer, influenza, hemoptysis, leryngopharyngitis, hernia, cough and respiratory diseases and are also used as an expectorant and antiscorbutic. [3][4][5] Veronica species contain mainly iridoid glucosides, especially benzoic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…cuneifolia and V. cymbalaria hemoptysis, laryngopharyngitis, hernia, cough, and respiratory diseases, and are also used as an expectorant and antiscorbutic (Tomassini et al, 1995;Su et al, 1999;Grahamet et al, 2000). Earlier investigations performed on Veronica species resulted in the isolation mainly of iridoid glucosides, especially benzoic and cinnamic acid esters of catalpol, some phenylethanoid, and flavonoid glycosides (Chari et al, 1981;Taskova et al, 1998;Harput et al, 2002aHarput et al, , 2002bSaracoglu et al, 2002;Jensen et al, 2005). In this study, Veronica cuneifolia subsp.…”
Section: Research Articlementioning
confidence: 82%
See 3 more Smart Citations
“…cuneifolia and V. cymbalaria hemoptysis, laryngopharyngitis, hernia, cough, and respiratory diseases, and are also used as an expectorant and antiscorbutic (Tomassini et al, 1995;Su et al, 1999;Grahamet et al, 2000). Earlier investigations performed on Veronica species resulted in the isolation mainly of iridoid glucosides, especially benzoic and cinnamic acid esters of catalpol, some phenylethanoid, and flavonoid glycosides (Chari et al, 1981;Taskova et al, 1998;Harput et al, 2002aHarput et al, , 2002bSaracoglu et al, 2002;Jensen et al, 2005). In this study, Veronica cuneifolia subsp.…”
Section: Research Articlementioning
confidence: 82%
“…The radical scavenging activity was determined by comparing the absorbance with that of blank (100%) containing only DPPH and solvent. All the analyses were done in 3 replicates (Hatano et al, 1989;Harput et al, 2002a;Kostadinova et al, 2007;Jensen et al, 2010).…”
Section: Dpph Radical Scavenging Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] Our previous research on this plant has demonstrated that the water soluble portion of MeOH extract has a suppressive effect on nitric oxide production in lipopolysaccharide-stimulated mouse peritoneal macrophages due to its free radical scavenging activity, and the chloroform soluble portion of MeOH extract shows cytotoxicity against KB and B16 cells. 14) Continuing our studies on bioactive constituents of Veronica species, we here examine V. persica and isolate a new phenylethanoid glycoside, termed persicoside (1) together with eleven known compounds: acteoside (2), 15) isoacteoside (3), 16) lavandulifolioside (4), 17) dulcitol (5), aucubin (6), 18) veronicoside (7), 19) amphicoside (8), 20) 6-O-veratroyl-catalpol (9), 21) catalposide (10), 20) verproside (11) 22) and verminoside (12). 23) This paper describes the isolation and the structure determination of the new phenylethanoid along with its free radical scavenging activity against 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical.…”
mentioning
confidence: 99%